(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate, type and grade bone marrow fibrosis in malignant disorders affecting bone marrow by using Reticulin and Van Gieson stain. Study Design: Descriptive / cross- sectional study. Place and Duration of Study: This study was conducted at the Haematology and Histopathology Department of Sheikh Zayed Hospital, Lahore from January 2013 to December 2014. Materials and Methods: Paraffin embedded trephine blocks of 80 consecutive patients diagnosed with malignant disorders affecting bone marrow were taken, sections were made and stained with Reticulin and Van Gieson trichrome stain. Grading of bone marrow fibrosis was done using European consensus 2005 (EC 2005) on bone marrow fibrosis. All data was entered and analyzed by using SPSS 20 .Types and grades of fibrosis were reported by using frequency and percentages. Results: In a total of 80 patient studied, 64 (80%) patients showed bone marrow fibrosis. Grade-1 fibrosis (MF-1) was seen in 50% grade-2 (MF- 2) was seen in 26.25% and grade-3 (MF- 3)was seen in 3.75 % of patients. Secondary bone marrow fibrosis was present in 62 (97%) of 64 cases and primary bone marrow fibrosis was seen in 2 (3%) of 64 cases. Conclusion: Eighty percent of patients with various malignant disorders affecting bone marrow had some degree of bone marrow fibrosis. Grade-1 fibrosis (MF-1) was the most common, seen in 50% followed by grade-2 (MF- 2) seen in 26.25% and grade-3 (MF- 3) seen only in 3.75 % of patients..